Upsetting the apple cart: Within-team profiles of intragroup conflict and their associations with narcissism. (November 2022) - Boulter, Matt W.; Roberts, Ross; Hardy, James
Abstract: Different types of intragroup conflict (i.e., relationship, task, and process conflict) co-exist in team environments yet how this co-existence is expressed is poorly understood, particularly in sports teams. Further, there is a lack of knowledge surrounding the antecedents of intragroup conflict. Here, we examined the nature of conflict profiles in sports teams and investigated narcissism as an antecedent to the conflict profiles. In a large, multi-group sample (n = 1107 athletes from 109 teams), participants completed measures of intragroup conflict and narcissism. Team-level latent profile analysis of intragroup conflict variables indicated five distinct within-team conflict profiles which varied in patterns of relationship, task, and process conflict. Moreover, teams high in narcissism (both in terms of team mean and team maximum scores) were more likely to occupy dysfunctional conflict profiles, that is profiles high in all conflict types. These findings underscore the importance of considering conflict profiles within teams and provide the first evidence for narcissism as a contributing factor in the development of conflict profiles in groups. Highlights: Five profiles of relationship, task, and process conflict exist within sport teams. Narcissism linked to profiles containing elevated relationship and process conflict levels. Maximum and mean team narcissism scores associated with conflict profiles.